Cost of health inequality to the NHS in Wales - Kadel, Rajendra; Allen, James; Darlington, Oliver; Masters, Rebecca; Collins, Brendan; Charles, Joanna M.; Asaria, Miqdad; Dyakova, Mariana; Bellis, Mark; Cookson, Richard (Frontiers in Public Health, 2022)
Background: Forty years from the seminal work of Welsh GP Julian Tudor Hart on the Inverse Care Law, inequalities in health and healthcare remain deeply embedded in Wales. There is a wider gap (over 17 years) in healthy life expectancy between people living in the most and least deprived neighbourhoods in Wales. This health inequality is reflected in additional healthcare use. In this study we estimate the cost of inequality associated with this additional healthcare use to the publicly funded National Health Service (NHS) in Wales. Methods: We retrieved administrative data on all NHS inpatient admissions, outpatient and accident and emergency attendances in Wales between April 2018 and March 2019 from Digital Health and Care Wales (DHCW). Hospital service use data were translated to costs using Healthcare Resource Group (HRG) and health service specific unit cost data and linked with area level mid-year population and deprivation indices in order to calculate the healthcare costs associated with socioeconomics deprivation. Results: Inequality in healthcare use between people from more and less deprived neighbourhoods was associated with an additional cost of £322 million per year to the NHS in Wales, accounting for 8.7% of total NHS hospital expenditure in the country. Emergency inpatient admissions made up by far the largest component of this additional cost contributing £247.4 million, 77% of the total. There are also substantial costs of inequality for A&E attendances and outpatient visits, though not maternity services. Elective admissions overall have a negative cost of inequality, since among men aged 50 to 75 and women aged 60 to 70, elective utilisation is actually negatively associated with deprivation. Conclusion: There are wide inequalities in health and healthcare use between people living in more deprived neighbourhoods and those living in less deprived neighbourhoods in Wales. Tackling health inequality through a combination of health promotion and early intervention policies targeted towards deprived communities could yield substantial improvement in health and wellbeing, as well as savings for the Welsh NHS through reduced use of emergency hospital care.